MORAL ACCOUNTABILITY AND SOCIAL NORMS. Issue 1 (4th December 2018) - Van Schoelandt, Chad
Abstract: This essay argues that moral accountability depends upon having a shared system of social norms. In particular, it argues that the Strawsonian reactive attitude of resentment is only fitting when people can reasonably expect a mutual recognition of the justified demands to which they are being held. Though such recognition should not typically be expected of moral demands that are thought to be independent of any social practice, social norms can ground such mutual recognition. On this account, a significant part of a society's social norms are also properly seen as moral norms. The essay defends this overlap of social and moral norms in contrast to views on which moral norms and social norms are sharply distinguished. Lastly, the essay concludes by addressing challenges for accountability in circumstances of norm change.